2019
DOI: 10.1016/j.tcr.2019.100236
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid approach to complex vascular injury secondary to blast induced scapulothoracic dissociation

Abstract: Scapulothoracic dissociation is a rare but devastating injury complex involving high velocity blunt trauma to the osseous, muscular, neurologic, and vascular structures of the shoulder girdle. Often seen following a motor vehicle or motorcycle accident, this injury complex presents with vascular trauma in over 80% of cases. We present a unique case of scapulothoracic dissociation secondary to a self-inflicted shotgun wound to the shoulder, not previously reported in the literature. The patient presented in hem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…In the last decade, evidence in the literature has supported ORIF for cases of STD ( Table I ). 1 , 10 , 12 , 13 , 15 , 17 , 19 , 23 Lal et al reported the case of a 32-year-old male who sustained a Zelle 2B STD following a motor vehicle accident. They performed ORIF with successful recovery of a nearly full ROM in the shoulder postoperatively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the last decade, evidence in the literature has supported ORIF for cases of STD ( Table I ). 1 , 10 , 12 , 13 , 15 , 17 , 19 , 23 Lal et al reported the case of a 32-year-old male who sustained a Zelle 2B STD following a motor vehicle accident. They performed ORIF with successful recovery of a nearly full ROM in the shoulder postoperatively.…”
Section: Discussionmentioning
confidence: 99%
“…Approximately 52% of patients with STD will have complete loss of motor and sensory functions in the affected extremity. 1 , 10 Since STD is rare, it is difficult to create a treatment algorithm that fully captures and appropriately weighs all possible factors. However, improved decision-making aids are needed, as clinicians have voiced concerns that singular factors, such as MESS scores, are inadequate for choosing treatment and predicting outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Once vascular injury was identified, surgery including autogenous vein and synthetic graft implantation or endovascular repair should be implemented [Desai 2014]. Recently, endovascular technique has been utilized in more trauma patients, due to its advantages, which could avoid surgical dissection in a traumatized area and significantly decrease the risk of injury to adjoined structures [Jordan 2019]. Research with 1143 trauma patients from 22 institutions in America revealed that endovascular therapy was highly applied among severely injured blunt trauma patients; this was associated with lower incidence of complications and better clinical prognosis [Faulconer 2018].…”
Section: Discussionmentioning
confidence: 99%